Effect of Orthodontic Brackets on the Accuracy of Apex Locators: A Pilot Study. (26th April 2021) - Şen, Özgür Genç; Ulusoy, Özgür İlke; Paltun, Yelda Nayır; Ulusoy, Çağrı
Abstract : The purpose of this study was to evaluate the effect of metal orthodontic brackets on the accuracy of electronic apex locator (EAL). The actual canal lengths (ACL) of 40 mandibular incisor teeth were determined. Then, the teeth were randomly divided into two groups (n = 20 ). Orthodontic metal brackets were applied in the first group, and no brackets, in the second group. The working length of each tooth was measured with an EAL under 3 test conditions according to the distance between the lip clip and sample tooth. Data were analyzed using one-way repeated measures analysis of variance and Tukey's post hoc tests (p = 0.05 ). In the bracketed samples, when the lip clip was located at 1 cm and 2 cm from the samples. The mean differences between the EAL measurements and ACLs were statistically higher than those when the samples were located 3 cm from the lip clip (p < 0.05 ). There were also statistically significant differences between EAL measurements and ACLs in the bracketed samples located 1 and 2 cm from the lip clip (p < 0.05 ). In the nonbracketed group, the differences between EAL measurements and ACLs were not statistically significant in the samples located 1, 2, and 3 cm from the lip clip (p > 0.05 ). Use of orthodontic metal brackets can negatively influence the accuracy of the electronic apex locator when the distance between the lip clip and bracket was short. A minimum of 3 cm distance should be kept between the lip clip and tooth in order to make consistent electronic measurements.